Kurgans of the 10th Century Near the Village of Sumarokovo, Smolensk Region - Vladimir Enukov (Нижневолжский археологический вестник)
In 1985, a research team of the Smolensk expedition of Moscow State University investigated two large kurgans with cremations on a slope near the village of Sumarokovo. Kurgan 2 was particularly difficult to construct. A log structure was erected on a specially prepared site (fill, ritual fire). During its filling with soil, burials 1 and 2 were made, and a fire was lit on the surface of the resulting platform, after which cremated remains of a man and a woman were poured out (burial 3). In addition to fragments of an early pottery vessel, it contained a handbag with overlays, a necklace of numerous beads and other finds. The kurgan is dated to the mid-950s – 970s. Kurgan 4, significantly damaged by foxholes, contained 3 burials, accompanied by intact and broken early pottery. It was probably erected earlier than kurgan 2. Sumarokovo is one of the so-called “round kurgans” of the Upper Dnieper region, which reflect the formation of the Old Russian culture that replaced the culture of the Smolensk long kurgans. The burial ground is located within the boundaries of a polity of the “chiefdom” type with its centre in Gnezdovo. Kurgan 2 attracts special attention. It did not contain weapons or luxury items, but a complex and labour-intensive set of rituals, joint cremation with the owner of a rich necklace, along with synchronous accompanying burials, suggest an extraordinary social status for the man.